Has HSR improved territorial cohesion in Spain? An accessibility analysis of the first 25 years: 1990–2015. Issue 3 (4th March 2019) - Monzon, Andres; Lopez, Elena; Ortega, Emilio
ABSTRACT: High Speed Rail (HSR) in Spain began in 1992 and currently has a network of some 3200 km. In this 25-year period, accessibility has progressively increased, changing its spatial distribution throughout the country. However, improvements in the HSR network may or may not have contributed to a more balanced territorial distribution of accessibility levels. These distributional effects of HSR have important implications for territorial cohesion, which is a strategic planning goal for transport infrastructures in the European Union. This paper presents a methodology for evaluating 'accessibility-based' territorial cohesion effects of HSR corridors. Accessibility values are calculated for successive five-year periods. Territorial cohesion effects are assessed based on changes in accessibility patterns and their spatial distribution. The results show that new HSR lines have significantly increased the accessibility levels of the Spanish population to most destinations. On average accessibility values have improved in the 1990–2015 period by 48.6% due to HSR, with differences among locations depending if they are or not nodes of the HSR network. The study's findings show also a more balanced distribution of accessibility, with 15% reduction in the dispersion of accessibility values between 1990 and 2015, implying a positive contribution to territorial cohesion goals.